Penanganan Tindak Pidana Kejahatan Premanisme di Wilayah Hukum Indragiri Hilir - Ali Azhar; Maryanto Maryanto; Vivi Arfiani Siregar (Universitas Kuningan, 2020)
The phenomenon of street crime in Indragiri Hilir began to develop and is undeniable, this phenomenon gave birth to a group of criminals who commit violence. Prema violence in maintaining its existence, both in the social and economic fields. Because the economy is increasingly difficult and the higher the level of poverty. Thugs in the jurisdiction of the Indragiri Hilir Police Station began to increase in the area of community life. The purpose of this study is to determine the constraints and implementation of Law Enforcement on Thuggish Actions. This research method uses an empirical juridical approach, which means reviewing the state of the problem in the field is associated with applicable legal aspects and regulating the problem. The results of thugs in the jurisdiction of the Indragiri Hilir Police Station began to increase in the area of community life. Thugs do extortion (voluntary) with extortion on a voluntary or voluntary basis from the merchant community, the private community, especially in Tembilahan City. The number of cases of gangsterism in 2014 there were 27 cases of violent crime. the investigation process contained 21 cases, 21 cases were submitted to the prosecutor's officeKeywords: Criminal Thugs; Law enforcement; Public order AbstrakFenomena kejahatan jalanan di Indragiri Hilir mulai berkembang dan tidak dapat disangkal, fenomena ini melahirkan sekelompok penjahat yang melakukan kekerasan. Kekerasan prema dalam mempertahankan eksistensinya, baik di bidang sosial maupun ekonomi. Karena ekonomi semakin sulit dan semakin tinggi tingkat kemiskinan. Preman di wilayah hukum Kantor Polisi Indragiri Hilir mulai meningkat di bidang kehidupan masyarakat. Tujuan dari penelitian ini adalah untuk mengetahui kendala dan implementasi Penegakan Hukum atas Tindakan Premanisme. Metode penelitian ini menggunakan metode pendekatan yuridis empiris, yang berarti meninjau keadaan masalah di lapangan dikaitkan dengan aspek-aspek hukum yang berlaku dan mengatur masalah. Hasil penelitian Preman di wilayah hukum Kantor Polisi Indragiri Hilir mulai meningkat di bidang kehidupan masyarakat. Preman melakukan pemerasan (sukarela) dengan pemerasan atas dasar sukarela atau sukarela dari komunitas pedagang, komunitas swasta, khususnya di Kota Tembilahan. Jumlah kasus premanisme pada 2014 ada 27 kasus kejahatan dengan kekerasan. proses penyelidikan berisi 21 kasus, 21 kasus telah diserahkan ke kantor kejaksaanKata Kunci: Tindak Pidana Premanisme; Penegakan Hukum; Ketertiban Umum.